Designing An Accounting System Using Microsoft Access For Toko Yanto - Budi Chandra; Viona Angelina (Universitas Internasional Batam, 2023)
A computer-based accounting system was designed for Toko Yanto in order to assist in inputting their everyday operational transactions. Before this system was made, Toko Yanto used manual bookkeeping as their accounting system. The activity was implemented from September to December 2022. The methods used were observation, interviews, and documentation. The accounting system is designed by using Microsoft Access. The implemented system can help business owner in avoiding inconsistency as well as human errors in recording their daily transactions. The system is also designed to display the output in the form of reports such as payables report, receivables report, stock report, purchase report, sales report, income statement, and statement of financial position. The result of the output presented can help business owner in their decision making for further business development. A recommendation for the future is to add other features that can make the system works even more efficiently and effectively.